The Influence of the Selection System, Training and Job Satisfaction on Employees Performance on PT Lion Air Group of Mutiara Sis Al-Jufri Palu Airport before the Pandemic Covid 19 - Rika Suprapty; R Syamsuddin; Maria Asri (Universitas Jember, 2020)
This study aims to determine and analyze the effect of the selection, training and employment systems. satisfaction both collectively and partially on the performance of employees at PT Lion Air Group from Mutiara Sis Al-Jufri Airport, Palu before the pandemic covid - 19. Data was collected through direct observation and surveys by distributing questionnaires and interviews to employees of PT. Lion Air Group Mutiara Sis Al-Jufri Palu before the pandemic covid -19 to become a plague in Indonesia. The analytical method used is multiple linear regression analysis. The test results show that the selection system, training and job satisfaction, both simultaneously and partially have a significant effect on employee performance before the spread of the covid-19 pandemic in Indonesia. Keywords: Selection System, Training, Job Satisfaction, Employee Performance, Covid 19